La esfinge y la literatura finisecular: Oedipe et le sphinx de Péladan - Macías-Villalobos, Cristóbal (My University, 2015)
In this paper we analyse the role of the mythological monster called the Sphinx in the play entitled Oedipe et le Sphinx by French writer Joséphin Péladan, which was performed in 1903. Here the Sphinx not only symbolizes the Femme Fatale, one of the most repeated topics in late nineteenth-century literature, but it also reveals its human nature and feelings under the guise of a monster.
Keywords: Péladan, Josephine - Crítica e interpretación; Joséphin Péladan; Oedipus myth; The Sphinx; The Femme Fatale; Human nature; Feelings